Art in Meaning: Implicature in The Movie Bolehkah Sekali Saja Ku Menangis by Reka Wijaya Kusuma - Isnaeni setyoningsih; Anas Ahmadi (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The purpose of this research is to explore and analyze the various types of implicature found in the film's dialogue, as well as how these implicatures contribute to the understanding of the psychological themes presented. The method used in this study is descriptive qualitative, where data is collected through transcripts of conversations in the film and analyzed to identify conventional, non-conventional, and contextual implicatures. The results of the study show that this film not only presents an engaging story but also delves into the depths of the characters' emotions and psychological conflicts through meaningful dialogue. The identified implicatures provide insights into the relationships between characters and broader themes regarding human experiences, thereby enriching the audience's understanding of the psychological issues faced by individuals in social contexts, with several types of implicature being conventional, non-conventional, and contextual. This film raises an inspiring psychological theme.